ANALISIS VARIABEL-VARIABEL YANG MEMPENGARUHI KEPUTUSAN UNTUK BERWAKAF TUNAI - Nanda Anggih Pratiwi; Multifiah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to analyze the influence of the variables religious compliance, motivation, income, information media access, and knowledge of waqf on the decision to give cash waqf donation. This study method used a quantitative approach with logistic regression analysis. The data obtained were primary data sourced from the results of the questionnaires that have been distributed. The sample number in this study was 70 respondents, both cash waqf and non-cash waqf. The results of this study indicated that variables of religious compliance, information media access, and knowledge of waqf partially had a significant effect on the decision to give cash waqf donation. While the motivation and income variables partially had no significant impact on the decision to give cash waqf donation.